Neuroterus paradecrescens, a new species of oak gall wasp from Mexico (Hymenoptera: Cynipidae: Cynipini) - García-Martiñón, Rosa D.; Bravo-Cuautle, Samay; Pérez-Torres, Betzabeth C.; Aragón-García, Agustín; Equihua-Martínez, Amando; Venegas, Edith G. Estrada-; Cuesta-Porta, Víctor; Melika, George; Romero-Rangel, Silvia; Pujade-Villar, Juli (Zootaxa, 2026)
A new species of oak gall wasp, Neuroterus paradecrescens García-Martiñón & Pujade-Villar sp. nov. is described. The description is based on the asexual female generation, that induces galls on the leaves of different endemic oak species of section Quercus. Galls are very similar to Neuroterus saltatorius var. decrescens from Arizona (USA). Diagnosis, distribution and data on the biology of the new species are given. This species represents one of the smallest species of gall wasps.